Organización contable en la empresa perfiles Catacocha de la Sra. León Castro Astrid Deyanira, periodo octubre - diciembre de 2023. - Armijos Castillo, Cecilia Paulina (2024)
The Curricular Integration Work entitled: Accounting Organization in the company Perfiles Catacocha of Mrs. León Castro Astrid Deyanira, period October - December 2023, was carried out to apply accounting, through the development of main and auxiliary records to generate information that contributes to knowing the economic and financial situation. The methodology is based on a mixed approach, explorative qualitative, descriptive, non-conventional, deductive, inductive, analytical, and synthetic methods, as well as observation and bibliographic collection techniques, which contributed to the collection of theoretical-practical data. A detailed accounting plan and a manual of accounts were designed that exhaustively records debit and credit transactions, as well as the balances of each account belonging to the items of assets, liabilities, equity, income, and expenses with their corresponding description. An initial inventory was drawn up with the verification of each of the assets, securities, and liabilities of the company. Purchase, sale, bank account, and transport invoices were analyzed, generating auxiliary records, which allowed all transactions to be summarized in a daily ledger where they were recorded chronologically and in the form of accounting entries. Subsequently, the accounts were recorded and a summary of the economic transactions with their respective values in the general ledger was executed, then the sums and balances were transferred to the trial balance, completing the necessary adjustments in the worksheet; Finally, the financial statements were made starting from the income statement to the cash flow. In conclusion, an accounting organization was made so that the company has a systematic process of the main operations, financial statements, and profitability of the company.